ANALISIS FUNGSI KOGNITIF PADA LANSIA DITINJAU DARI JENIS KELAMIN, RIWAYAT PENDIDIKAN, RIWAYAT PENYAKIT, AKTIVITAS FISIK, AKTIVITAS KOGNITIF, DAN KETERLIBATAN SOSIAL - Arti Febriyani Hutasuhut; Marisa Anggraini; Reza Angnesti (JURNAL PSIKOLOGI MALAHAYATI, 2020)
ANALYSIS OF COGNITIVE FUNCTIONS IN ELDERLY IN TERMS OF GENDER, EDUCATION HISTORY, DISEASE HISTORY, PHYSICAL ACTIVITY, COGNITIVE ACTIVITIES, AND SOCIAL ENGAGEMENTOne of the disorders caused by degeneration in the elderly is cognitive impairment This study aims to determine the factors that influence cognitive function in the elderly in the work area of the Kedaton Bandar Lampung Health Center in 2018. This research is an analytical survey with a cross-sectional approach. The research subjects were 107 elderly people living in the working area of the Kedaton Health Center in Bandar Lampung. Data in this study were obtained through interviews using questionnaires, social disengagement scale, and MMSE. Data analyzed using chi-square test. The results showed that there was a significant relationship between education, history of illness, physical activity, cognitive activity, and social involvement with cognitive function, whereas for sex, no significant relationship was found with cognitive function.Salah satu gangguan akibat degenerasi pada lansia yaitu gangguan kognitif. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi fungsi kognitif pada lansia di wilayah kerja Puskesmas Kedaton Bandar Lampung tahun 2018. Penelitian ini merupakan survey analitik dengan pendekatan cross-sectional. Subyek penelitian adalah 107 orang lansia yang tinggal di wilayah kerja Puskesmas Kedaton Bandar Lampung. Data dalam penelitian ini diperoleh melalui wawancara menggunakan kuesioner, skala social disengagement, dan MMSE. Analisis data menggunakan uji chi-square. Hasil penelitian menunjukan bahwa terdapat hubungan yang signifikan antara pendidikan, riwayat penyakit, aktivitas fisik, aktivitas kognitif, dan keterlibatan sosial dengan fungsi kognitif, sedangkan untuk jenis kelamin, tidak ditemukan hubungan signifikan dengan fungsi kognitif.